Faktor Penyebab dan Upaya Penyelesaian Klaster 3 Backlog Pendaftaran Tanah Sistematik Lengkap di Kabupaten Tojo Una-Una, Sulawesi Tengah: - - Irawan, Trio; Nugroho, Tanjung; Supama, Yohanes; Kusmiarto, Kusmiarto; Suhendro, Suhendro; Suharto, Eko; Wulan Titik Andari, Dwi (Sekolah Tinggi Pertanahan Nasional, 2025)
Systematic Complete Land Registration (PTSL) is a national program aimed at accelerating and completing the first-time land registration process simultaneously across Indonesia through the